The impact of nonmotor symptoms on quality of life in patients with Parkinson's disease in Taiwan - Liu WM (Dove Medical Press, 2015)
Weng-Ming Liu,1,2 Ru-Jen Lin,1 Rwei-Ling Yu,3 Chun-Hwei Tai,1 Chin-Hsien Lin,1 Ruey-Meei Wu1 1Department of Neurology, National Taiwan University Hospital, College of Medicine, National Taiwan University, Taipei, Taiwan; 2Department of Neurology, Buddhist Tzu Chi General Hospital, Hualien, Taiwan; 3Institute of Behavioral Medicine, College of Medicine, National Cheng Kung University, Tainan, Taiwan Purpose: The nonmotor symptoms (NMS) of Parkinson’s disease (PD) are important factors for quality of life (QoL). Few studies on NMS have been conducted in Asian PD patients. Additionally, effects of anti-PD drugs on risk of NMS are still controversial. We therefore conducted this hospital-based cross-sectional study to examine the clinical factors, including concomitant anti-PD medication use, on the occurrence of NMS and QoL in Taiwanese PD patients.Patients and methods: PD patients who received long-term follow-up in the movement disorders clinics were enrolled and received NMS questionnaire (NMSQuest) and the 39-item Parkinson’s Disease Questionnaire (PDQ-39). Spearman’s rank correlation coefficient was checked for the correlation between clinical factors and NMSQT/PDQSI. Multiple linear regressions were applied to assess the influence of clinical factors on NMSQT/PDQSI.Results: A total of 210 PD patients (mean age 66.1±9.86 years, Hoehn and Yahr stage 2.2±0.9) were included in this study. Up to 98% of patients reported at least one symptom of NMS. The most prevalent symptom was urinary complaints (56%), followed by memory/apathy (30%) and depression/anxiety (28%). The correlation between NMSQT and PDQSI was strong (rs=0.667), especially the item of depression/anxiety (rs=0.607). The regression model for NMSQT indicated that disease duration and severity, but not pharmacological therapy, were major predictors of NMS.Conclusion: Our data indicated a high prevalence rate of NMS in PD patients. Among symptoms of NMS, depression and anxiety had the greatest impact on QoL. Concomitant anti-PD medication use did not affect the occurrence of NMS and QoL. Keywords: NMS, NMSQuest, NMS questionnaire, PD, PDQ-39, PDQSI